The Effect of Using Canva Learning Media on Students' Learning Motivation in Economics Subject at SMA Negeri 1 Peusangan Selatan - Nisa Husna; Mira Chairani; Intan Zuhra (Universitas Ibn Khladun Bogor, 2026)
The goal of this study was to determine if and how the use of Canva in the Economics class at SMA Negeri 1 Peusangan Selatan influenced the students' motivation to study. The study was quantitative in nature and employed an experimental design with a control group that was not equal. Saturation sampling was used to choose participants from the population of eleventh graders. Data was collected using a 20-item Likert-scale survey that evaluated students' motivation to learn. Before it was used, the instrument was tested for validity and reliability. The data was subjected to a battery of tests using IBM SPSS Statistics version 22, including validity, reliability, normality, homogeneity, and independent sample t-tests. An average motivation score of 38.38 was achieved by the experimental group, which was marginally higher than the control group. But the independent sample t-test findings (Sig. = 0.387 > 0.05) show that neither group is significantly different from the other. Thus, there was no discernible effect of Canva on students' economics study motivation. Canva showed promise for making the classroom more interesting, even if the impact was not statistically significant. We suggest that future research use Canva with active learning models, use bigger samples, and extend treatment durations to get a more complete picture.